REFLECTIONS ON SUBJECTIVITY IN CIVIL ENGINEERING PRACTICE - Teles, Mairla Meneses Lopes (Editora Impacto Científico, 2025)
Since the 1990s, several studies have highlighted the importance of seeking to understand the influence of subjectivity on professional performance. In this article, we present the result of a basic qualitative exploratory research on subjectivity in the daily practice of civil engineering from the representations of three professionals interviewed. In the light of the comprehensive interpretation, elements were sought to understand, essentially, how the engineer emotionally perceives his workday, and how those professional deals with emotions in his journey. The interviews revealed that the routine of this profession is characterized by frustration, anxiety, and strong demotivation, which inevitably compromises the performance and contributes to psychic-emotional illness in the profession. It is understood that a better treatment of the subject is necessary since graduation and in continued qualification to make professionals more prepared to deal with subjectivity in their daily lives, in view of the self-perception of incapacity and emotional exhaustion reported as constant in this area in which subjectivity is not even discussed and in which performance is linked only to rational aspects, which are insufficient for understanding of the complex nature of being and its dimensions of action.DOI: https://doi.org/10.56238/edimpacto2025.089-008